Pemanfaatan Teknologi Informasi dan Edukasi Gizi Menggunakan Aplikasi Gizi Anakku untuk Pencegahan Stunting di Desa Makmur - Sherllia Sofyana; Gabriella Sakulat; Matius Paundanan (LPPM Universitas Widya Nusantara, 2025)
Stunting is a chronic nutritional problem that affects children's growth and cognitive development. This community service activity aimed to improve nutritional literacy and the use of the